Enantiopure nanohoops through racemic resolution of diketo[n]CPPs by chiral derivatization as precursors to DBP[n]CPPs. Issue 30 (1st July 2021) - Wassy, Daniel; Hermann, Mathias; Wössner, Jan S.; Frédéric, Lucas; Pieters, Grégory; Esser, Birgit
Abstract : Racemic resolution of diketone-embedded cycloparaphenylenes by derivatization with a chiral auxiliary provides scalable access to enantiopure hoops with chiroptical properties. Abstract : Strained conjugated nanohoops are attractive synthetic targets due to the bending of their π-system, which leads to intriguing optoelectronic properties, among others. By incorporating non-mirror-symmetric aromatic panels, chiral nanohoops can be obtained. We herein present a strategy to enantiopure nanohoops by racemic resolution through chiral derivatization of diketone-embedded hoops. The resulting diketo[ n ]CPPs ( n = 6, 7) contain two stereogenic carbon atoms each and possess high fluorescence quantum yields paired with circularly polarized luminescence. These are versatile precursors to chiral dibenzo[ a, e ]pentalene-based nanohoops DBP[ n ]CPPs with antiaromatic character and ambipolar electrochemical behavior. Due to their strained structures the DBP[ n ]CPPs do not racemize at room temperature, which is supported by high calculated isomerization barriers. X-ray crystallographic investigations on the DBP[ n ]CPPs and their precursors as well as DFT calculations provide insight into the build-up of strain energy during the synthetic transformations.